Association Analysis of SNPs in GRHL2 and RORA Genes with Lambing Number in Small-Tailed Han Sheep - Xiufen Pu; Kai Liu; Xiangyu Wang; Ran Di; Xiaoyun He; Yufang Liu; Mingxing Chu (Animals)
As one of the essential reproductive traits in sheep, the lambing number directly affects the economic benefits of the sheep breeding industry [...]